(3GdJShjb GdSjGMj GdMOjK (B/s - (3ebGHdI, NGdOs; (3GdSQGHj, YdGA s ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2000)
(3eONd Gdi GdJShjb GdSjGMj(B-(3SjQI GdYedGA GdSdhcjI(B-(3JbSje GdShb GdSjGMj(B-(3fXGe GdeYdheGJ GdSjGMj hHMhK GdJShjb(B-(3JNWjW hJfejI GdefJL GdSjGMj(B-(3GSJQGJjLjI GdefJL GdSjGMj(B-(3GSJQGJjLjI GdJSYjQ GdSjGMj(B-(3GSJQGJjLjI GdJhRjY GdSjGMj(B-(3GSJQGJjLjI GdJQhjL GdSjGMj(B-(3GSJQGJjLjI GdJShjb GdSjGMj GdTGedI(B-(3GdJShjb GdSjGMj HhGSWI GdGfJQfJs
(3HHdhZQGajG U(B.303s
Keywords: (3GdGSJQGJjLjIs; (3GdGfJQfjJs; (3GdJShjbs; (3GdSjGMIs